2, 5-Dimethoxy-1, 4-Benzoquinone (DMBQ) as Organic Cathode for Rechargeable Magnesium-Ion Batteries. Issue 3 (13th January 2016) - Pan, Baofei; Zhou, Dehua; Huang, Jinhua; Zhang, Lu; Burrell, Anthony K.; Vaughey, John T.; Zhang, Zhengcheng; Liao, Chen
Abstract : 2, 5-Dimethoxy-1, 4-benzoquinone (DMBQ) was reinvestigated as a cathode material with magnesium electrolytes that are capable of plating/stripping magnesium for rechargeable magnesium-ion batteries. Two electrolytes, the magnesium bis(trifluoromethylsulfonyl)imide mixed with MgCl2 in dimethoxyethane (Mg(TFSI)2 -2MgCl2 in DME) electrolyte, and the Mg(TFSI)2 in diglyme were selected. The Mg(TFSI)2 -2MgCl2 in DME enabled Mg-DMBQ batteries with a discharge potentials above 2.0 V vs Mg/Mg 2+, which is superior to the previous reported potential in Mg-DMBQ batteries with conventional magnesium salt-based electrolytes (1.1 V, vs Mg/Mg 2+ ), and also excels the well-known Chevrel phase Mo6 S8 in magnesium-ion batteries (1.2 V, vs Mg/Mg 2+ ).